Real-Time Car Crash Detection and Notifier Using GPS Module and IoT - Abu Seman, Muhammad Luqman Hakim; Sudin, Nor'aisah (Multidisciplinary Applied Research and Innovation, 2025)
With the increasing number of vehicles in Malaysia year by year, accident can occur to anyone no matter how safely the person drive, the other driver might be the cause of the accident and some even have the misfortune that nobody knows that the person get caught in accident and probably need a few days before being found. With the help of this project, it will instantly notify the family members of the victim that their beloved one gets caught in an accident and can let them reach the victim as soon as possible. This project makes use of IoT concept where it sends data through the internet. With the help of ESP32 microcontroller, that makes the data transmitting possible along with the GPS Module Neo-8M to point to the accident location. The collision sensors and the gyroscope sensor MPU6050 act as the input device for the main device. The main function of collision sensors is to detect any potential vehicle(car) crash, while gyroscope sensor MPU6050 is used to detect the orientation of the vehicle whether it is in normal orientation or otherwise. Then, the accident location will be displayed on the mobile application which has been developed in this project as well. The evaluation on the accuracy of the GPS module in pointing out the location of the accident location also has been conducted in four different environments, in an open area, inside the building, between high-rise building and wooded area. Based on the results obtained, it is shown that the accuracy of the GPS module in an open area is accurate meanwhile in other environments, a slight error occurred where the highest approximate value is five meters off from the location in real time.